Порівняння методів оцінювання ефективності інвестиційних проектів - Брінь, Павло Володимирович; Сіробаба, Яна Геннадіївна (НТУ "ХПІ", 2016)
У статті проводиться досліджується сутність оцінювання ефективності інвестиційної діяльності, проводиться порівняння методів оціню-вання ефективності інвестиційної діяльності, зокрема розглядаються особливості застосування статичних та динамічних методів, розглядаються переваги та недоліки їх застосування. Окремо розглядаються особливості застосування динамічних методів оцінювання ефективності інвестиційної діяльності менеджментом промислових підприємств.

The purpose of article is determination of features of application of methods of an assessment of efficiency of investment activity.The article explores the essence of investment activity effectiveness evaluating, the comparison of methods of investment activity effectiveness assessing is done, the features of the application of static and dynamic methods are described, advantages and disadvantages of the methods are analyzed, the features of the application of dynamic methods for evaluating the effectiveness of investment by management are described. Though there is a number of prob-lems in the course of application of dynamic methods of an assessment, but they are more exact that causes expediency of th eir application.
Comparison of methods for evaluating the effectiveness of investment projects
Keywords: діяльність інвестиційна; ефективність економічна; методи статичні; методи динамічні; дисконтування; потік грошовий; аналіз фінансовий; investment performance; dynamic methods; static methods